Marination liquids enriched with probiotics and their inactivation effects against food-borne pathogens inoculated on meat. (December 2021) - Gargi, Ahmet; Sengun, Ilkin Yucel
Abstract: The aim of the study was to develop marination liquids (MLs) enriched with probiotics ( Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus rhamnosus or their combination) to improve the safety and sensory quality of meat during marination. The total acidity, total phenolic content, antioxidant and antimicrobial activities of MLs were in the range of 0.70–0.92 g tartaric acid/100 mL, 331.00–513.80 mg GAE/L, 71.10%–93.37% and 6.50–10.00 mm, respectively. At the end of the marination, the numbers of Escherichia coli O157: H7, Listeria monocytogenes and Salmonella Typhimurium on meat samples (≅6 log CFU/g) were decreased in the range of 0.7–2.7, 2.1–3.3 and 0.8–2.0 log CFU/g, respectively, depending on the type of ML and the treatment time used. Additionally, meat sample marinated with MLs containing L . casei was the most preferred sample in terms of appearance, color, flavor and general acceptability. These results showed that the existing effects of koruk juice were increased by probiotics. Highlights: Probiotic enriched marination liquids (MLs) were developed to improve meat safety. Bioactive and antimicrobial properties of MLs were increased by probiotics. The most effective ML against pathogens inoculated on meat was ML2. The most sensitive pathogen to MLs is L. monocytogenes on meat. The meat marinated with ML2 was the most liked sample in terms of sensory properties.